PENGARUH KUALITAS PELAYANAN DAN KERELASIAN NASABAH TERHADAP CITRA BANK BANTEN - Winna Sarikusumaningtyas; Sugeng Prayetno (Media Bina Ilmiah, 2023)
Competition between banks is getting tougher, where more and more banks are involved in fulfilling customer needs and desires, causing each bank to place an orientation towards customer satisfaction as the main goal. That's what the Banten Bank faced. The decline in the market share of Bank Banten's savings products tends to be an indication that Bank Banten's image is still not good enough. Likewise, the image of Bank Banten which is still relatively unfavorable is allegedly due to the poor quality of services provided, so that Bantenese people who have become Bank Banten savings customers do not provide recommendations to colleagues or family to become Bank Banten savings customers. Bank Banten's relatively unfavorable image is also allegedly caused by the lack of Bank Banten in establishing good relationships with customers. The findings in this study are that service quality and customer relations have a joint effect on the description of Bank Banten, but when viewed partially, it turns out that customer relations in general affect the image of Bank Banten, while service quality does not affect the image of Bank Banten.